2014
DOI: 10.1002/2014jc009829
|View full text |Cite
|
Sign up to set email alerts
|

Subtidal variability in water levels inside a subtropical estuary

Abstract: Year-long time series of water level are analyzed at five locations along the St. Johns River Estuary, Florida, to investigate propagation of subtidal pulses. Hilbert-transformed Empirical Orthogonal Functions (HEOFs) are obtained after a dominant seasonal signal is extracted from the data. These functions provide information on spatial structure and propagation phase of subtidal water level pulses. The first HEOF mode explains 96% of the subtidal variability and features an unusual spatial structure: amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…The development and widespread use of nonstationary tidal analysis methods (Appendix A gives a brief overview of methods used to calculate tidal components) match the present-day research effort to understand the interactions of river discharge with tides. River discharge influences both the tidal and subtidal water levels (Alebregtse & de Swart, 2016;Henrie & Valle-Levinson, 2014;Jay & Flinchem, 1997;Ross & Sottolichio, 2016), enhances tidal friction, thereby damping tidal energy and tidal range (Cai et al, 2012(Cai et al, , 2014Godin, 1991;Savenije et al, 2008), decreases wave celerity (Godin, 1985;Savenije et al, 2008), and controls tidal interactions by dissipating the principal tidal constituents and favoring energy transfer from the principal bands to the lower and higher frequencies (Guo et al, 2015(Guo et al, , 2016. This generation of overtides and compound tides is favored until they reach a point upstream where they are damped more rapidly by friction than they are generated through the nonlinear interactions (Matte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The development and widespread use of nonstationary tidal analysis methods (Appendix A gives a brief overview of methods used to calculate tidal components) match the present-day research effort to understand the interactions of river discharge with tides. River discharge influences both the tidal and subtidal water levels (Alebregtse & de Swart, 2016;Henrie & Valle-Levinson, 2014;Jay & Flinchem, 1997;Ross & Sottolichio, 2016), enhances tidal friction, thereby damping tidal energy and tidal range (Cai et al, 2012(Cai et al, , 2014Godin, 1991;Savenije et al, 2008), decreases wave celerity (Godin, 1985;Savenije et al, 2008), and controls tidal interactions by dissipating the principal tidal constituents and favoring energy transfer from the principal bands to the lower and higher frequencies (Guo et al, 2015(Guo et al, , 2016. This generation of overtides and compound tides is favored until they reach a point upstream where they are damped more rapidly by friction than they are generated through the nonlinear interactions (Matte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A study for a semienclosed homogeneous, rotating basin by Sanay and Valle‐Levinson (), investigated the wind effect on hydrodynamics. Subtidal flows in estuaries and subtropical lagoons have been examined with ADCP data in many studies (e.g., Henrie & Valle‐Levinson, ; Li et al, ; Murphy et al, ; Sepulveda et al, ). In these studies, however, the wind effects were discussed without attention to the details of the weather systems.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that can modify salinity distribution are, among others, the variability of river discharge by dam regulation and precipitation fluctuations and by changes in depth through sea‐level rise or dredging (van Rijn, 2011). The effects of sea‐level rise in an estuary may be explored by understanding the interactions of river discharge and forcing from the ocean at tidal and subtidal time scales (Henrie & Valle‐Levinson, 2014). Subtidal time scales refer here to any periods greater than tidal periods, that is, >26 hr.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present work is to study phase propagation in tidal and subtidal signals. It has been demonstrated that subtidal pulses from the ocean do propagate along estuaries (Henrie & Valle‐Levinson, 2014). Wind‐induced subtidal levels over the continental shelf (e.g., set‐up or set‐down) may propagate along estuaries in the form of free waves (Wong & Valle‐Levinson, 2002) with periodicities of 2–4 days or even longer, such as 5–20 days (Garvine, 1985).…”
Section: Introductionmentioning
confidence: 99%